2019
DOI: 10.5194/acp-2019-367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liquid-liquid phase separation and viscosity within secondary organic aerosol generated from diesel fuel vapors

Abstract: <p><strong>Abstract.</strong> Information on liquid-liquid phase separation (LLPS) and viscosity (or diffusion) within secondary organic aerosol (SOA) is needed to improve predictions of particle size, mass, reactivity, and cloud nucleating properties in the atmosphere. Here we report on LLPS and viscosities within SOA generated by the photooxidation of diesel fuel vapors. Diesel fuel contains a wide range of volatile organic compounds, and SOA generated by the photoox… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 91 publications
4
17
1
Order By: Relevance
“…In addition, (iv) the surface tension for sucrose and AS are available in the literature (Grayson et al, 2015;Dutcher et al, 2010). The lower limits of these physical parameters for all solutions, used in this study, fall within the range of the lower limits used in previous studies that used the same technique, i.e., poke-and-flow (Renbaum-Wolff et al, 2013b;Grayson et al, 2015;Song et al, 2016aSong et al, , 2019Song et a., 2021). Therefore, the lower limit of the viscosity was defined as ~10 8 Pa‧s when a particle cracked during poke-and-flow experiments.…”
Section: S2 Measurements Of Viscosity Using Poke-and-flow Techniquesupporting
confidence: 59%
“…In addition, (iv) the surface tension for sucrose and AS are available in the literature (Grayson et al, 2015;Dutcher et al, 2010). The lower limits of these physical parameters for all solutions, used in this study, fall within the range of the lower limits used in previous studies that used the same technique, i.e., poke-and-flow (Renbaum-Wolff et al, 2013b;Grayson et al, 2015;Song et al, 2016aSong et al, , 2019Song et a., 2021). Therefore, the lower limit of the viscosity was defined as ~10 8 Pa‧s when a particle cracked during poke-and-flow experiments.…”
Section: S2 Measurements Of Viscosity Using Poke-and-flow Techniquesupporting
confidence: 59%
“…Most studies of viscosities and the related physical states of aerosol particles have been carried out by means of laboratory studies, because there are almost no direct instruments to quantify the viscosities of ambient, airborne submicronand supermicron-sized aerosol particles. Numerous laboratory studies on viscosities and physical states undertaken so far have focused on organic aerosols with different types of secondary organic aerosols investigated (Virtanen et al, 2010;Kuwata and Martin, 2012;Perraud et al, 2012;Renbaum-Wolff et al, 2013a;O'brien et al, 2014;Bateman et al, 2015;Song et al, 2015;Athanasiadis et al, 2016;Grayson et al, 2016;Hosny et al, 2016;Song et al, 2016a;Yli-Juuti et al, 2017;Ham et al, 2019;Petters et al, 2019;Song et al, 2019;Gervasi et al, 2020;Song et al, 2021). These studies showed that the viscosities of organic aerosol particles can vary depending on RH and chemical composition leading to different physical states, including amorphous solid (glassy), (semi-)solid, as well as liquid-like phases.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted ambient viscosity is compared with the experimental observed viscosity of SOA formed from isoprene (Song et al, 2015), α-pinene (Abramson et al, 2013;Renbaum-Wolff et al, 2013;Kidd et al, 2014;Pajunoja et al, 2014;Zhang et al, 2015;Grayson et al, 2016;Petters et al, 2019), toluene (Song et al, 2016a) and diesel fuel (Song et al, 2019). The majority of experimental values are well bounded by the predicted viscosity of OOA, represented by the pink shaded area.…”
Section: Tgorg At 11 Global Sitesmentioning
confidence: 96%
“…Predicted viscosity of (a) HOA, COA and BBOA and (b) LO-OOA, MO-OOA, IEPOX SOA and Isoprene OA in different locations at 298 K as a function of RH. Experimentally measured viscosity of laboratory-generated SOA formed from isoprene (Song et al, 2015), α-pinene (Abramson et al, 2013;Renbaum-Wolff et al, 2013;Kidd et al, 2014;Pajunoja et al, 2014;Bateman et al, 2015;Zhang et al, 2015;Grayson et al, 2016;Petters et al, 2019), toluene (Song et al, 2016), and diesel fuel (Song et al, 2019) are also shown. Predicted viscosity of IEPOX-derived OS mixtures (solid blue line) is from Riva et al (2019).…”
Section: Author Contributionmentioning
confidence: 96%
See 1 more Smart Citation